Aktuelle Bestandsabschätzungen wirtschaftlich wichtiger Grundfischarten im Nordostatlantik - Schöne, Rüdiger (1995)
Assessments on stocks of cod, haddock, saithe, redfish and Greenland halibut were carried out by the "Arctic Fisheries Working Group" in August 1995. The most important results are given in this report. Johann Heinrich von Thünen-Institut, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010